Identification and bioinformatics analysis of the DUS gene in Eimeria media - Yijin Zou; Yiyan Wang; Diyi Duan; Xun Suo; Yuanyuan Zhang (BMC Veterinary Research)
Abstract This study aims to explore the coding sequence (CDS) of the putative DUS gene in Eimeria media and assess its potential biological functions during the parasite's lifecycle. Initially, oocysts were isolated from fecal samples of rabbits infected with E. media, from which DNA and RNA were extracted. These extractions were used as templates for PCR to successfully amplify the CDS of the DUS gene, confirming its presence within the E. media genome. Further analysis using quantitative PCR (qPCR) demonstrated significantly higher expression of the DUS gene in the precocious line (PL) compared to the wild type (WT). This differential expression highlights a potential functional role for the DUS gene in influencing the development and sporulation processes of E. media, which may contribute to the precocious phenotype. Additionally, bioinformatics analysis provided insights into the evolutionary trends and structural characteristics of the DUS gene across different species, suggesting a broader biological significance. The elevated expression of the DUS gene in the PL suggests its critical involvement in the growth and reproductive processes of the parasite. This finding opens new avenues for research aimed at controlling E. media infection through targeted interventions in the DUS gene expression pathways.